Performance of shading device inspired by traditional hejazi houses in Jeddah Saudi Arabia - Batterjee, Sara Adel (2010)
With the recent economic boom in Saudi Arabia many new high-rise buildings, residential compounds and social complexes are under construction. Designing these buildings without respect to the residents‟ social and religious needs creates a problem in the development toward globalization and acceptance of resulting urban change. This research seeks to propose a solution through the development of a shading device inspired by an environmental control architectural element of window shading, found in traditional Hejazi architecture of Saudi Arabia called al Roshan, that provides the physically desirable amount of natural-lighting and maintains socially-accepted visual privacy. Five shading device design cases were proposed, and different parameters manipulated and tested for natural-lighting lux levels using Ecotect and Radiance software. The first design case succeeded in providing comfortable natural-lighting levels. In addition, the design‟s cooling efficiency, when calculated and compared with the traditional Roshan in the same tested room, provided comfortable natural-lighting levels for North, South and West directions. It was also the best approach for most eastern orientations, except during the early morning hours. As it succeeded in reducing 50 % of the cooling loads compared to the traditional Roshan design, the proposed shading device was shown to be an energy-efficient solution.